Nutraceuticals for Cardiovascular Risk Related-Obesity, the Role of Mufa Avocado: A Scoping Review - Nyono Dedi Prabowo; Diah Kurnia Mirawati; Setyo Sri Rahardjo (Global Health Science Group, 2023)
Obesity and its complications are a major nutritional problem worldwide, broadly impacting various organ systems. It causes a negative effect on the risk of obesity-induced cardiovascular disease (CVD). Guidelines recommend MUFA in dietary therapy for obesity and CVD. However, little literature has focused on the potential of avocado as a nutraceutical in obesity-induced CVD, particularly related endothelial dysfunction. Therefore, a scoping review is required. The aim was to review the role of MUFA contained in the avocado diet on obesity-related CVD risk. This scoping review was performed using the 5-step Arkeys and O’Malelev framework and reported according to PRISMA ScR. Four electronic databases were searched systematically. Articles are included if eligible. The result was descriptive and narrative synthesized. A total of 513 articles were collected. Three studies of Randomized Control Trials met the inclusion criteria. Overall, nutrients contained in the avocado act as nutraceuticals. Especially monounsaturated fatty acid (MUFA) oleic can help improve endothelial dysfunction and ultimately reduce the risk of CVD. Available evidence suggests role MUFA contained avocado has the potential as a nutraceutical of dietary therapy to improve endothelial dysfunction associated with reducing obesity-induced CVD risk.